An Efficient Synthesis of Medium-size Heterocycles Fused to Aryl Rings, Benzazepan, Benzazocan and Benzazonan-1-ones by Friedel-Crafts Acylation - MENATI, S.; SAIAHY, S. (Asian Journal of Chemistry, 2010)
Since 7,8,9-membered heterocyclic compounds such as benzazepan, benzazocan and benzazonan-1-ones are important systems in medical and industrial technology, we tried to prepare such heterocycles through simple and effective reactions using amino acids as precursor.